A Study on General Awareness on Power of Police to Investigate Under Criminal Procedural Code Among Individuals from Different Place of Living - B, LEELESH SUNDARAM.; SUNDARAM, ASHA; GAYATHRI, R.; PRIYA, V. VISHNU (The journal of contemporary issues in business and government, 2020)
For decades, across the country, there has been an ongoing debate on the powers and the steps taken for law enforcement by the police. Statistics prove that people oppose the steps taken by the police even when it is done under their official capacity. Though the CRPC, has given a well crafted and apt powers to the police for the purpose of investigation, several media reports prove that individuals are against the process of investigation carried out by the police this situation seems magnified in the case of rural areas, and thus an ambiguity arises as to whether the procedure requires amendment or are the general public not aware of the same. The study aims to find out the general awareness of individuals on the powers of police to investigate under crpc, using non probability convenience sampling and chi square tests. The study reveals that individuals in the urban areas are aware that the police may extend the duration but the individuals in rural areas are not aware of the same. In case of cognizable offence order of magistrate is not necessary, individuals in the urban areas are aware of this power whereas those in the rural areas aren’t aware. The people living in urban areas are aware that the police officer has got the power to subject the victim and the accused for medical examination but it is not in the case of rural areas. Thus it could be stated that there is a relationship between Awareness of General Public on Power of Police to Investigate under Criminal Procedural Code and place of living. It could be recommended that that awareness programs may be organized in rural areas by police and lawyers so that the negative perception over the police may change